Analisis Dampak Penggunaan Dana Desa terhadap Pembangunan Ekonomi Pedesaan di Kecamatan Pandawan Kabupaten Hulu Sungai Tengah Tahun 2016 - Nofian, Muhammad Faisal (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
The research was conducted to (1) Analyze the impact of village funds onrural economic development in terms of the adequacy of village funds in financingvillage development and the suitability of village funding expenditures by villagemeetings Pandawan Sub-district ; (2) To analyze the views of the community on theuse of village funds for the economic development of society in rural PandawanDistrict.The results of this study indicate that the village funding program is beneficialin rural economic development such as with the results of respondents 53% ofrespondents stated enough help in the economic growth after the village fundprogram, which village funds have a role in improving rural infrastructure and it tosupport the financial activities of rural communities. Furthermore, the real income ofthe city also increased is also mainly due to the impact of the village fundingprogram; the neighborhood of 69% also recognizes it said that their incomeincreased so that the effect of the use of village funds for rural economic developmenthas been running well whose benefits can be felt directly by the surroundingcommunity.